If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(+5)=3(x-1)
We simplify the equation to the form, which is simple to understand
-3(+5)=3(x-1)
Reorder the terms in parentheses
+(-15)=3*(x-1)
Remove unnecessary parentheses
-15=+3+*(+x-1+)
Reorder the terms in parentheses
-15=+(+3x-3)
Remove unnecessary parentheses
-15=+3x-3
We move all terms containing x to the left and all other terms to the right.
-3x=-3+15
We simplify left and right side of the equation.
-3x=+12
We divide both sides of the equation by -03 to get x.
x=-4
| -3+4x=-35 | | 5x^6=-320 | | 5m+3=9-4m | | 5x+6=2-3x | | 2(2y+7)-9y=-2(3-5y)+5 | | 10+6x=46 | | 2x+7=14+5x | | 16=3x+3 | | 100/5/2*5=16 | | 8x+9=2(7x-6) | | 13*4-22/11+5*x=75 | | 40+3x=-20 | | (3+w)w+w+(3+w)=24 | | 2x-5=34+x | | 7(c-9)=9(2c-8)+4 | | iman=5 | | 3x^2-6x-5=4 | | 12-5u= | | 3x^4-4x^2-1=0 | | lg(2x+40)=1.75 | | 8x+3(20-x)=125 | | 57.50-8=49.50 | | a+1/2=1 | | 731848618382638+7782658236472634972347692= | | 2(x-1)+10x=5(2x+3)+4 | | factorx^2-3x+1=0 | | x^2+2*(k-3)*x+(k-1)=0 | | 4(2x+5)+9v=36 | | 4x-8-2x=2(x-4) | | ax+b=2x | | A+3=b | | 7x+4=-x+-10 |